Reviev paperManagement of venous leg ulcers – modern wound dressings - Żmudzińska, Maria; Czarnecka-Operacz, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Venous leg ulcers arising from pathophysiological processes appearing in the course of chronic venous insufficiency can be classified also as the chronic wounds, which is due both to the character and the duration of the disease. Moreover, this term indicates possible therapeutic difficulties. Topical treatment should be considered as one of the contributing factors of the comprehensive venous leg ulcers management. Modern topical treatment methods are based on the active wound dressings applications. The characteristics of the ideal active wound dressing have been described. Active wound dressings are classified according to their structure, characteristics and treatment indications. We present the survey of the active wound dressings groups taking into consideration their components, characteristics and treatment indications.